Effect of Nail Size, Insertion, and Δ Canal-Nail on the Development of a Nonunion After Intramedullary Nailing of Femoral Shaft Fractures. Issue 11 (November 2019) - Serrano, Rafael; Mir, Hassan R.; Gorman, R. Allen; Karsch, Jordan; Kim, Ryan; Shah, Anjan; Maxson, Benjamin; Infante, Anthony; Watson, David; Downes, Katheryne; Sanders, Roy W.
Abstract : Objective: To determine whether intramedullary nail (IMN) diameter, antegrade versus retrograde insertion, or the difference between the canal and IMN diameter affect femoral shaft fracture healing. Design: Retrospective analysis of a prospective database. Setting: Level One Regional Trauma Center. Patients/Participants: Seven hundred thirty-three femoral shaft fractures (OTA/AO 32) treated with an IMN between 1999 and 2017. After exclusion criteria, 484 fractures remained in the final analysis. Intervention: Closed section, cannulated, interlocked, titanium alloy IMN using a reamed insertion technique. Main Outcome Measurements: Nonunion, IMN size (10, 11.5, and 13 mm), antegrade versus retrograde insertion, Δ canal-nail diameter (ΔD) after reaming (<1, 1–2, or >2 mm). Results: IMN diameters used were as follows: 314/10 mm (64%), 137/11.5 mm (28%), and 33/13 mm (8%). Forty-five percent were placed in antegrade versus 55% retrograde. Four hundred fifty-six fractures (94.2%) healed uneventfully. There were no IMN failures. 10/484 IMNs (2%) had broken interlocking screws; only 4 were associated with a NU. Average time to union was 23 weeks (12–119). Twenty-eight (5.8%) developed NU. There was no statistical correlation between (1) the NU rate and IMN diameter: 10 mm, 6.3%; 11.5 mm, 5.1%; 13 mm, 3% ( P = 0.8, power = 0.85), (2) the NU rate and ΔD: 7.1% <1 mm, 5.6% 1–2 mm, 20% >2 mm ( P = 0.36), (3) the NU rate and fracture location: Prox = 11%, Mid = 5%, Dist = 3% ( P = 0.13), or (4) the NU rate and antegrade (7.2%) versus retrograde (4.2%) insertion ( P = 0.24). Conclusion: Similar healing rates occurred regardless of IMN diameter, Δ canal-nail diameter after reaming, or insertion site. This indicates that a closed section, cannulated, interlocked, titanium alloy IMN with a diameter of 10 mm can be considered the standard diameter for the treatment of acute femoral shaft fractures, regardless of entry point. This should be associated with less reaming and therefore shorter operative times, and possibly less hospital implant inventories as well. Larger diameter IMN should be reserved for revision surgery. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.